DETECTION OF DIGENERATIVE DISEASES IN JOMBLANG SUB-DISTRICT, SEMARANG CITY - Devi Etivia Purlinda (Wealth Community Empowerment, 2024)
One of the people's lifestyles causes changes in disease patterns from infectious to non-communicable. Non-communicable diseases such as Stroke, Coronary Heart Disease (CHD), Cancer and Diabetes Mellitus (DM) were ranked highest. Objective: conduct a health check including weight and height measurements to determine Body Mass Index (BMI) so that it can detect obesity, blood glucose level measurement detects DM, blood pressure detects hypertension, cholesterol detects hypercholesterolemia. Hemoglobin and hematocrit levels determine anemia in productive age people. The method of community service for Health Examination is measuring blood glucose levels, blood pressure, cholesterol, hemoglobin and hematocrit in Jomblang Village Employees of productive age of 15-55 years and consulting the results of health examinations, consulting nutrition and conducting health promotion. Analytical discriptive to describe blood glucose levels, blood pressure, cholesterol, hemoglobin and hematocrit of Jomblang Village employees aged 15-55 years.